Difference between 5A score and the HOPE score - Yohei Okada; Tasuku Matsuyama; Kei Hayashida; Shuhei Takauji; Jun Kanda; Shoji Yokobori (Journal of Intensive Care, 2022)
Abstract Recently, a letter to the editor was published to comment on the 5A score which is the prediction model for accidental hypothermia patients comparing the HOPE score. In this letter, we responded to the comments to clarify the difference between the 5A score and the HOPE score.